Displaced children of Europe, then and now: photographed, itinerant and obstructed witnesses. (27th May 2018) - Gigliotti, Simone
ABSTRACT: The displaced children of Europe, who live in and through landscapes and in temporary accommodations—their bare worlds of life stuffed into rucksacks—are our constant companions, their movement and immobility paraded as a geopolitical inconvenience and security threat to governments and officials even before they embark on treacherous Mediterranean sea and land crossings to hoped-for asylum in Europe. Gigliotti examines the humanitarian ambitions and changing narrative authority in the coverage of displaced children in the photography of David 'Chim' Seymour, notably from his UNICEF/UNESCO-commissioned tour of Europe in the summer of 1948 and, briefly, in UNICEF's online platform, 'Refugees in Europe: Then and Now'. She outlines the post-war historical context of internationalism and humanitarian engagement with the visual to advocate for displaced children's rights to place, home and belonging, and concludes with an analysis of the representation of the post-war refugee and displaced person as a memory emissary in today's refugee crises.